A Desconstituição de paternidade e o direito ao estado de filiação: uma análise dos conflitos filiatórios à luz da jurisprudência do Superior Tribunal de Justiça - SANTOS, Lorena de Fatima Oliveira dos (2022)
This paper aims to demonstrate the changes that have taken place in family law over time, as well as the evolution of the family and its affiliation to our legal system, especially considering the constitutional principles that are most relevant to the topic, such as the principle of human dignity and the principle of affectivity. In this sense, the criteria for determining paternity will be analyzed, which are the legal, biological and socio-affective criteria, in order to demonstrate that the figure of the father is more important than that of the genitor, considering that it is the figure of the first one that most contributes to the moral and psychic development of the child. Although it is expected that parents and children are in harmony, it is common that there are conflicts between them, mainly because more attention is given to the biological criteria than the socio-affective. In this sense, it is important that in situations of filiatory conflict, the best interest of the child and adolescent is respected, besides the welfare of each individual.